2021
DOI: 10.1186/s13100-021-00233-3
|View full text |Cite
|
Sign up to set email alerts
|

RIP-seq reveals LINE-1 ORF1p association with p-body enriched mRNAs

Abstract: Background Long INterspersed Element-1 (LINE-1) is an autonomous retroelement able to “copy-and-paste” itself into new loci of the host genome through a process called retrotransposition. The LINE-1 bicistronic mRNA codes for two proteins, ORF1p, a nucleic acid chaperone, and ORF2p, a protein with endonuclease and reverse transcriptase activity. Both proteins bind LINE-1 mRNA in cis and are necessary for retrotransposition. While LINE-1 transcription is usually repressed in most healthy somatic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 72 publications
0
35
0
Order By: Relevance
“…Both proteins are required for L1 retrotransposition and assemble with their encoding L1 mRNA in cis, forming a cytoplasmic ribonucleoprotein particle (L1 RNP), that represents a retrotransposition intermediate [7,[13][14][15][16][17][18]. L1 RNPs associate with cytoplasmic stress granules and processing bodies (Pbodies) [18][19][20][21], but the role of these cellular structures in the L1 life cycle is still controversial. L1 RNPs, but also L1ORF1p alone, colocalize with various other RNA-binding proteins and for many of these proteins an RNA-dependent interaction with L1ORF1p has been reported [18,19,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both proteins are required for L1 retrotransposition and assemble with their encoding L1 mRNA in cis, forming a cytoplasmic ribonucleoprotein particle (L1 RNP), that represents a retrotransposition intermediate [7,[13][14][15][16][17][18]. L1 RNPs associate with cytoplasmic stress granules and processing bodies (Pbodies) [18][19][20][21], but the role of these cellular structures in the L1 life cycle is still controversial. L1 RNPs, but also L1ORF1p alone, colocalize with various other RNA-binding proteins and for many of these proteins an RNA-dependent interaction with L1ORF1p has been reported [18,19,[21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…L1 RNPs associate with cytoplasmic stress granules and processing bodies (Pbodies) [18][19][20][21], but the role of these cellular structures in the L1 life cycle is still controversial. L1 RNPs, but also L1ORF1p alone, colocalize with various other RNA-binding proteins and for many of these proteins an RNA-dependent interaction with L1ORF1p has been reported [18,19,[21][22][23][24][25][26]. The retrotransposition cycle also involves trafficking of L1 RNPs into the nucleus, which requires the endosomal sorting complex required for transport (ESCRT) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments suggest activity of LINE-1 elements in epithelial cells [16]. In vitro experiments have shown that, in conditions of high LINE-1 derepression and expression, the machinery that mediates LINE-1 retrotransposition, can mobilize other sequences such as Alu and SVA elements, and can even lead to integration of certain cellular mRNAs, leading to the formation of processed pseudogenes [17][18][19][20]. One study even showed that LINE-1 elements can promote the low frequency integration of certain RNA viruses [21].…”
Section: Introductionmentioning
confidence: 99%
“…Out of these three gRNAs, we chose to use gRNA 4 and gRNA7 for our C-BERST assay. While gRNA 8 also showed high specificity to L1Hs, it did not fully align with an active L1Hs sequence that we previously identified to be expressed in LNCaP cells (Xp22.2(2)) [ 21 ]. Since Xp22.2(2) was one of the highest LINE-1 loci expressed in LNCaP cells, we decided to exclude it as a guide.…”
Section: Discussionmentioning
confidence: 95%
“…ORF1p is a nucleic acid chaperone that forms homotrimers and binds LINE-1 mRNA [ 18 , 19 ]. ORF1p has also been shown to bind ssDNA as well as non-LINE-1 mRNAs [ 20 , 21 ]. ORF2p’s endonuclease and reverse transcriptase domains provide the enzymatic activity necessary for retrotransposition [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%